Electromagnetic assessment for mobile phone base stations at major cities in Malaysia - Ismail A.; Din N.M.; Jamaluddin M.Z.; Balasubramaniam N. (2023)
This paper describes a research carried out to study electromagnetic exposure emitted by mobile phone base stations in public areas at major cities in Malaysia, i.e. Kuala Lumpur and Johor Bahru. Two measurement methods, namely broadband and narrowband measurements were used for that purpose. The recorded power densities were then compared with the International Commission on Non-ionizing Radiation Protection (ICNIRP) guidelines. The measurements show that the electromagnetic exposures from mobile phone base stations are well below the ICNIRP limit. The highest recorded broadband measurement value was 2.17% of the worst case RF Maximum Permissible Exposure (MPE) value set by ICNIRP, which is 2 W/m2. For narrowband measurement, the highest total exposure ratio recorded was 0.3741% of the corresponding MPE. 2009 IEEE.